サイヒョウ カタ センパク ヨウ プロペラ ノ セッケイ ト ソノ モケイ シケン ニ ヨル ヒョウカ ニ ツイテ - 笹島, 孝夫; ササジマ, タカオ; 武隈, 克義; タケクマ, カツヨシ; 加用, 芳男; カヨウ, ヨシオ; Sasajima, Takao; Takekuma, Katsuyoshi; Kayo, Yoshio (1985)
P(論文) 氷海航行船舶の運航に際しては, 船体が破壊した氷片の中で作動するプロペラおよびその軸系の挙動は, 船舶本来の航行目的の達成, 安全確保上非常に重要である。このため, 氷海航行船舶用プロペラの設計には特に注意が払われてきた。本論文では, 砕氷型船舶用プロペラの設計手法についてレビューするとともに, 設計に対する基本的考え方に基づいて, 南極観測船「しらせ」について翼形状の異なる2つのプロペラを設計し, 模型試験により, 流体力学的特性および模擬氷による氷荷重試験を実施した結果について報告する。現在, 広く使用されている円弧翼型およびレンズ型(レーニン型)翼断面プロペラの流体力学的性能(単独特性およびキャビテーション性能), および氷荷重(アイスミリング荷重)が明らかとなり, 翼断面形状の実用的な選定のために有用なデータを提供している。 The propellers for ships operating in the Antarctic and Arctic regions encounter fragments of ice and sometimes are damaged according to the severity of ice load. The design of propellers for such ships is quite different from that of conventional ships, since in designing the propeller geometry, not only hydrodynamic performances requested are to be satisfied but also blades are to be strong enough to stand ice-milling load. This study deals with the effect of the geometry of the propeller on performances in open-water and in ice. Two candidate propellers with different blade shape, ogival and lenticular sections were designed for the Japanese icebreaker SHIRASE, by employing the existing ice-milling load estimation method of JAGODKIN and the blade-propeller shaft strength calculation method of IGNATJEV. The results show the specific features of each propeller blade section for propellers of icebreakers. Also, the existing methods for estimating the ice-load are found useful. departmental bulletin paper